Eryptosis is an indicator of hematotoxicity in the risk assessment of environmental amorphous silica nanoparticles exposure: The role of macromolecule corona. (15th August 2022) - Chen, Zhangde; Yang, Bingwei; Yan, Ziyi; Song, Erqun; Song, Yang
Abstract: Silica nanoparticles (SiO2 NPs) have been widely manufactured for various applications and unintentionally generated in various industrial processes. SiO2 NPs exposure is potentially hazardous to human health. Incremental evidence has indicated the presence of SiO2 NPs in systemic circulation, which warranted their interaction with blood components. Due to the obvious weakness of hemolysis in the risk assessment of environmental NPs, we for the first time use eryptosis as a sensitive indicator to assess the hematotoxicity of SiO2 NPs. In vitro results showed that the exposure of erythrocytes to pristine SiO2 NPs resulted in typical features of eryptosis, including oxidative stress, calcium influx, phosphatidylserine externalization and hemolysis. However, SiO2 NPs covered with mouse plasma (SiO2 @MP) or grafted with polyvinylpyrrolidone (SiO2 @PVP) did not stimulate eryptosis. Interestingly, neither bare nor macromolecule-decolorated SiO2 NPs caused eryptosis in our in vivo mouse model, highlighting the protective role of coronal proteins on the amelioration of SiO2 NPs-induced hematotoxicity. These results emphasized the influences of surface modification on the toxicity of environmental NPs. Graphical Abstract: ga1 Highlights: Pristine SiO2 NPs exposure caused eryptosis in vitro. SiO2 @MP and SiO2 @PVP did not stimulate eryptosis in vitro. In our in vivo mouse model, neither naked nor decorated SiO2 NPs caused eryptosis.